THE DEVELOPMENT OF COMIC-BASED PICTURE STORY MEDIA TO ENHANCE LEARNING MOTIVATION AMONG PRIMARY SCHOOL STUDENTS - Harni; Tri Murwaningsih; Sukarno (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The Indonesian language learning process in primary schools remains teacher-centred with limited teaching materials, meaning that pupils’ motivation to learn has not developed to its full potential. This study aims to (1) analyse the Indonesian language learning process, (2) develop comic-based PICSTOM (Picture Story Media), and (3) test the effectiveness of this medium in enhancing the learning motivation of primary school pupils. The study employed a research and development method using the 4D model, comprising the Define, Design, Develop, and Disseminate stages. The research subjects consisted of an experimental class at SDN 01 Gedong and a control class at SDN 03 Gedong. Data were collected through observation, learning motivation questionnaires, interviews, and documentation. The results of the study indicate that the comic-based Pistoria, media was deemed highly suitable based on validation by media experts, subject matter experts, and language experts. The effectiveness test showed that student learning motivation in the experimental class was higher than in the control class. This study provides practical significance as an innovative alternative for Indonesian language learning media, as well as a theoretical contribution to the development of story-based learning media in primary schools.